Impact of NaF during chloride treatment of CdTe solar cells. (1st March 2020) - Shalvey, Thomas P.; Major, Jonathan D.
Abstract: Sodium has shown promise as a p-type dopant in CdTe solar cells but reports of increased acceptor concentrations are typically accompanied by adverse structural and morphological changes. Here we show that these changes, which occur upon chlorine activation in the presence of sodium, are dependent upon the initial grain structure. We find that small grain CdTe films deposited by sputtering undergo extensive recrystallisation following MgCl2 treatment, whereas large grain CdTe deposited by close space sublimation (CSS) do not. This allowed the effect of NaF on device performance to be studied, which is shown to strongly enhance CdS–CdTe intermixing. This results in lower efficiencies due to inferior junction quality, without any clear change in acceptor concentration.